Controlling second-harmonic diffraction by nano-patterning MoS2 monolayers - Loechner, Franz J. F.; Mupparapu, Rajeshkumar; Steinert, Michael; George, Antony; Tang, Zian; Turchanin, Andrey; Pertsch, Thomas; Staude, Isabelle; Setzpfandt, Frank (Optics Express, 2019)
Monolayers of transition metal dichalcogenides have a strong second-order nonlinear response enabling second-harmonic generation. Here, we control the spatial radiation properties of the generated second harmonic by patterning MoS2 monolayers using focused ion beam milling. We observe diffraction of the second harmonic into the zero and first diffraction orders via an inscribed one-dimensional grating. Additionally, we included a fork-like singularity into the grating to create a vortex beam in the first diffraction order.
CRIS-Team Scopus Importer:2023-04-20